A SEMANTIC FEATURE ANALYSIS OF THE ENGLISH MODAL AUXILIARIES (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2022)
This article deals with a semantic analysis of the English Modal Auxiliaries and their both the epistemic and the deontic characteristics of modality.